2020
DOI: 10.3390/nu12071951
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction Mediates the Relationship between Perceived Stress and Body Mass Index in Taiwan Young Adults

Abstract: Perceived stress is the degree of stress experienced by an individual in the face of a stressor. Studies have shown that stress affects emotions, leads to behavioral changes, and is likely to trigger physical illnesses. According to the World Health Organization (WHO), stress is classified as a health epidemic of the 21st century; in the meantime, the percentage of adults being overweight and with obesity has continued to grow after reaching 38.9% in 2016. Hence, it is unclear whether perceived stress has beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Perceived stress interferes with eating behavior and can lead to increased food consumption [ 39 ]—this includes increased consumption, especially of foods high in calories and rich in sugar, fats, and salt [ 18 , 19 , 40 ]. In this study, 36.1% of respondents expressed that they had increased their frequency of consumption of some foods, while 14.1% were unsure whether they had done so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived stress interferes with eating behavior and can lead to increased food consumption [ 39 ]—this includes increased consumption, especially of foods high in calories and rich in sugar, fats, and salt [ 18 , 19 , 40 ]. In this study, 36.1% of respondents expressed that they had increased their frequency of consumption of some foods, while 14.1% were unsure whether they had done so.…”
Section: Discussionmentioning
confidence: 99%
“…Addictive behaviors include binge eating without subsequent compensation, continuous eating, even in small amounts (snacking), and the consumption of foods high in calories, sugars and fats, which can interfere with the limbic system of the brain. These behaviors, which can lead to an increase in body weight and thus body mass index (BMI), fall under the umbrella of “emotional eating” (i.e., the consumption of food in response to negative emotions without following hunger cues) [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was shown that among people up to 25 years of age there were statistically significantly fewer symptoms of FA than in other age groups. Most publications focus on the diagnosis of FA among the youth or student population [67][68][69]. One study found that the rate of FA and the number of symptoms in women aged 18-34, 35-54 and over 55 years of age were significantly higher than in men in the same age groups, and there was no significant difference between the groups [70].…”
Section: Discussionmentioning
confidence: 99%
“…Stress can disrupt eating behaviour and encourage eating high palatable foods [14]. Therefore, the activation of the reward circuit; hence the mesolimbic dopaminergic system secretes dopamine in the ventral tegmental area (VTA) [16,25].…”
Section: Discussionmentioning
confidence: 99%